2014
DOI: 10.1007/s40089-014-0133-4
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis of silver nanoparticles using keratinase obtained from a strain of Bacillus safensis LAU 13

Abstract: In this study, crude extracellular keratinase obtained from a novel keratin-degrading bacterial strain, Bacillus safensis LAU 13 (GenBank accession No. KJ461434) was used for the synthesis of silver nanoparticles (AgNPs). The particles were characterised by UVVisible spectroscopy, Fourier transform infrared (FTIR) spectroscopy, and transmission electron microscopy. The biosynthesised AgNPs exhibited maximum absorbance at 409 nm. They are spherical in shape with the size ranging 5-30 nm. The FTIR spectrum showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
80
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 150 publications
(95 citation statements)
references
References 38 publications
15
80
0
Order By: Relevance
“…6a), and this conforms with similar results earlier reported by several authors (Zaki et al 2011;Kannan et al 2013;Lateef et al 2015a). The particles were well dispersed, an indication of good stability to avoid aggregation.…”
Section: Biosynthesis and Characterization Of Agnpssupporting
confidence: 93%
See 4 more Smart Citations
“…6a), and this conforms with similar results earlier reported by several authors (Zaki et al 2011;Kannan et al 2013;Lateef et al 2015a). The particles were well dispersed, an indication of good stability to avoid aggregation.…”
Section: Biosynthesis and Characterization Of Agnpssupporting
confidence: 93%
“…The biosynthesized AgNPs displayed maximum absorbance at the wavelength of 436 nm (Fig. 2), which falls within the reported range of 391-440 nm for AgNPs (Thirumurugan et al 2011;Zaki et al 2011;Kannan et al 2013;Priyadarshini et al 2013;Lateef et al 2015a). It was observed that dilution ratio of 1:40 (extract:AgNO 3 solution), and pH 8.5 produced highest yield of AgNPs with maxima absorbance readings at 436 nm (Figs.…”
Section: Biosynthesis and Characterization Of Agnpssupporting
confidence: 82%
See 3 more Smart Citations